Anti‐hepatitis C virus compounds obtained from Glycyrrhiza uralensis and other Glycyrrhiza species - Myrna Adianti (Wiley-Blackwell, 2014)
Development of complementary and/or alternative drugs for treatment of hepatitis C virus (HCV) infection is still much needed from clinical and economic points of view. Antiviral substances obtained from medicinal plants are potentially good targets to study. Glycyrrhiza uralensis and G. glabra have been commonly used in both traditional and modern medicine. In this study, extracts of G. uralensis roots and their components were examined for anti‐HCV activity using an HCV cell culture system. It was found that a methanol extract of G. uralensis roots and its chloroform fraction possess anti‐HCV activity with 50%‐inhibitory concentrations (IC50) of 20.0 and 8.0 μg/mL, respectively. Through bioactivity‐guided purification and structural analysis, glycycoumarin, glycyrin, glycyrol and liquiritigenin were isolated and identified as anti‐HCV compounds, their IC50 being 8.8, 7.2, 4.6 and 16.4 μg/mL, respectively. However, glycyrrhizin, the major constituent of G. uralensis, and its monoammonium salt, showed only marginal anti‐HCV activity. It was also found that licochalcone A and glabridin, known to be exclusive constituents of G. inflata and G. glabra, respectively, did have anti‐HCV activity, their IC50 being 2.5 and 6.2 μg/mL, respectively. Another chalcone, isoliquiritigenin, also showed anti‐HCV activity, with an IC50 of 3.7 μg/mL. Time‐of‐addition analysis revealed that all Glycyrrhiza‐derived anti‐HCV compounds tested in this study act at the post‐entry step. In conclusion, the present results suggest that glycycoumarin, glycyrin, glycyrol and liquiritigenin isolated from G. uralensis, as well as isoliquiritigenin, licochalcone A and glabridin, would be good candidates for seed compounds to develop antivirals against HCV.